Performance Improvement of Vector Control Based Unsymmetrical Two-Phase Induction Generator with Optimum Voltage Compensation - Chaiwut Choorak; Vijit Kinnares; Chavaporn Bumroongphuck; Nuttapong Prapurt (International Review of Electrical Engineering (IREE), 2024)
This paper presents performance improvement with optimum voltage compensation of a vector control based unsymmetrical Two-Phase squirrel cage Induction Generator (TPIG) with closed loop speed control using carrier-based space vector pulse width modulation. Indirect Field-Oriented Control (IFOC) of the induction generator is used to achieve fast response and good accuracy. The proposed system consists of a two stage AC-DC-AC link equipped with bidirectional power flow between the machine and the single-phase grid. The DC link voltage is kept constant at the reference value by using hysteresis current control of the grid side converter resulting in rectification and inversion modes of operation with high-power factor and nearly sinusoidal current waveform. A Carrier-Based Space Vector Modulation (CBSVPWM) technique is used for controlling a two-phase three-leg voltage source converter providing balanced and unbalanced voltages with an optimum value of voltage compensation. The experimental results show that the system performance for unbalanced supplied voltages with the optimum value of the compensation of the machine is better than that for balanced supplied voltages in terms of power transfer to the grid, electromagnetic torque pulsation and speed ripple.
Keywords: Multilevel Inverters and Converters; Induction Heating and Inverter Technology; Advanced DC-DC Converters